Peran Edukasi Gizi Dalam Menurunkan Risiko Penyakit Tidak Menular Pada Karyawan Balai Pelatihan Kesehatan Provinsi Kalimantan Timur - Atting, Yenny; K., Iriyani; Wisnuwardani, Ratih Wirapuspita (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Hypertension and Diabetes Mellitus (DM) are non-communicable diseases (NCDs) with a high prevalence in Indonesia, one of the prevention efforts is through the NCD institution/workplace Posbindu which aims to detect early NCD risk factors. Nutrition education plays an important role in the management and prevention of complications from both diseases. The purpose of this community service is to increase the knowledge of employees of the East Kalimantan Provincial Health Education and Training Center about healthy eating through counseling. The activity, which was attended by 38 employees, management staff, cleaning services and security guards, showed positive results, where the level of understanding of participants regarding the diet for non-communicable diseases increased by 26%. In conclusion, this nutrition education program is effective and implemented continuously with various methods and media that are more varied as part of promotive and preventive efforts.